Low carbon city awards ceremony - UiTM, UGC (UiTM Green Centre, 2025)
Six buildings at UiTM Shah Alam have successfully achieved the diamond rating at the 2024 LCC2030C Low Carbon City Awards Ceremony held on 26 February 2025. The awarded buildings are the Tuanku Syed Sirajuddin Chancellery Building, College of Built Environment Studies, Academic Language Studies, UiTM Health Centre, Development Department Complex, and College of Computing Informatics and Mathematics Studies.